PERSONAL ORIENTATION OF HIGHER EDUCATION SCHOOLS AS A MEANS OF INCREASING THE LEVEL OF CREATIVE STUDENT ACTIVITIES - O.S. Bilous (Academy of Cognitive and Natural Sciences, 2006)
The article deals with the problem of improvement of the intended teacher's level of creative activity by means of personal orientation of classes in higher school as one of the factors of his professionally creative self realization.